Optimization of the Synthesis of 18F‐D2‐Deprenyl With Mild 18F‐Fluorination and Minimum Precursor Input for PET Imaging of Neuroinflammation. (11th August 2020) - Lee, Sang Ju; Ko, Na Re; Oh, Seung Jun
Abstract : Here, we established optimized conditions for a mild 18 F‐fluorination to yield 18 F‐deprenyl and 18 F‐D2 ‐deprenyl as neuroinflammation imaging agents by fully automatic synthesis. Initially, manual synthesis with 1 mg of precursor and pH = 7.8 KOMs elution buffer yielded 85–92% of 18 F‐incorporation yields and showed nondecay corrected yields of 15–17%. Fully automatic synthesis showed a nondecay corrected radiochemical yield of 10.7 ± 0.46%. Owing to low precursor input, the maximum molar activity achieved was 1302.4 ± 26.4 GBq/μmol. Our mild 18 F‐fluorination procedure showed higher radiochemical yields and molar activity than those by previously used procedures, even with minimized precursor input. Abstract : Radiochemical synthesis of 18F‐deprenyl and 18F‐D2‐deprenyl.